PENINGKATAN KEBERSIHAN GIGI DAN MULUT MELALUI PENGGUNAAN MEDIA FLIPCHART SISWA SD GMIM TUMPENGAN DESA SEA II KECAMATAN PINELENG - Novarita Mariana Koch; Ni Made Yuliana (Jurnal Kesehatan Gigi, 2021)
Dental and oral hygiene is a condition in which the teeth in the oral cavity are clean, free from plaque , debris, tartar and food scraps on the surface of the teeth as well as no bad breath. By cleaning from food debris left between the teeth, the dental and oral hygiene can be achieved properly. Health maintenance requires supporting facilities that can help attempt to improve the degree of oral health, one of which is by the use of media. Media or props are aids for the promotion of dental health that can be seen, heard, touched, or smelled in order to facilitate communication and disseminate information. This study aims to determine the effectiveness of using flipchart media in improving dental and oral hygiene among elementary students. We undertook the research at SD GMIM Tumpengan, Sea II Village, Pineleng District with a sample of 74 people. The study was conducted with an analytical survey with a cross-sectional study approach, using the T test. In conclusion, our work shows that flipcharts are effective in improving oral and dental hygiene.